Ecotoxicological potential of antibiotic pollution–industrial wastewater: bioavailability, biomarkers, and occurrence in Mytilus galloprovincialis - Zouiten, Amina; Beltifa, Asma; Van Loco, Joris; Mansour, Hedi Ben; Reyns, Tim (Environmental science and pollution research international, 2016)
Environmental pollution by pharmaceutical residues has become a major problem in many countries worldwide. However, little is known about the concentrations of pharmaceuticals in water sources in Tunisia. Residues in the natural environment have been of increasing concern due to their impact on bacteria resistance development and toxicity to natural communities and ultimately to public health. In this work, we collected the wastewater sample from a pharmaceutical industry, which specializes in the antibiotics manufacture, during the years 2014–2015. Generally, this effluent is discharged into the marine environment and causes environmental problems. The Mediterranean mussel Mytilus galloprovincialis was commonly used as a model organism for its peculiar morphofunctional properties which also make it an excellent marine environmental biomonitoring species. The histological sections of mussel, which are exposed at different dilutions of pharmaceutical wastewater (PW), indicate a large pathological power revealed on the gills. On the other hand, genotoxicity of the studied effluent was evaluated using comet assay for quantification of DNA fragmentation in gill cells. Results show that PW exhibited a statistically significant ( p < 0.001) genotoxic effect in a dose-dependent manner. However, the toxic effects of PW decreased significantly after its treatment with Bacillus atrophaeus . Toxicities can be imputed to the presence of antibiotics. In fact, chemical analysis of the gills of mussel M. galloprovincialis using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) showed the presence of some antibiotic residues. These concentrations decrease to half in mussels treated with PW biodegraded by B. atrophaeus .